High-energy and low-cost membrane-free chlorine flow battery - Hou, Singyuk; Chen, Long; Fan, Xiulin; Fan, Xiaotong; Ji, Xiao; Wang, Boyu; Cui, Chunyu; Chen, Ji; Yang, Chongyin; Wang, Wei; Li, Chunzhong; Wang, Chunsheng (Nature communications, 2022)
Grid-scale energy storage is essential for reliable electricity transmission and renewable energy integration. Redox flow batteries (RFB) provide affordable and scalable solutions for stationary energy storage. However, most of the current RFB chemistries are based on expensive transition metal ions or synthetic organics. Here, we report a reversible chlorine redox flow battery starting from the electrolysis of aqueous NaCl electrolyte and the as-produced Cl 2 is extracted and stored in the carbon tetrachloride (CCl 4 ) or mineral spirit flow. The immiscibility between the CCl 4 or mineral spirit and NaCl electrolyte enables a membrane-free design with an energy efficiency of >91% at 10 mA/cm 2 and an energy density of 125.7 Wh/L. The chlorine flow battery can meet the stringent price and reliability target for stationary energy storage with the inherently low-cost active materials (~$5/kWh) and the highly reversible Cl 2 /Cl − redox reaction. Flow batteries provide promising solutions for stationary energy storage but most of the systems are based on expensive metal ions or synthetic organics. Here, the authors show a chlorine flow battery capitalizing the electrolysis of saltwater where the redox reaction is stabilized by the saltwater-immiscible organic flow.